The Influence of Corporate Governance, Profitability, and Leverage on Profit Management - Feronika; Eny Purwaningsih (Global Writing Academica Researching and Publishing, 2022)
In the current development, the company can manage the company's funding properly so that the company avoids losses. This research aims to empirically determine the influence of corporate governance, profitability, and leverage on management in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research uses a type of causal research to determine the causal relationship of two or more variables. The sample in this research is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period using the purposive sampling method. 13 companies meet the research sample criteria, so a sample of 65 financial statements data is obtained. The research results simultaneously show the influence of corporate governance, profitability, and leverage on earnings management. They partially show that the size of the board of directors and the expertise of the audit committee do not affect earnings management. Meanwhile, the board of commissioners meeting and profitability variables hurt earnings management, while the leverage variable has a positive effect on earnings management